Pastoral Strategy in Developing the Dimension of Understanding Generation Z - Joni Manumpak Parulian Gultom; Fransiskus Irwan Widjaja; Martina Novalina; Ester Lina Situmorang; Yohana Natassha (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
The research center numbers released the results of the 2021 survey, where generation Z has the smallest spiritual index of 3.50, while the spiritual index of Indonesia is 3.79. The index of understanding dimensions is low, namely 3.13 for self-image and 3.40 for motivation. This paper aims to find a new pastoral strategy in reaching generation Z for self-image restoration and motor development. The next goal is to build synergy with parents in spiritual growth. This study uses a qualitative method with data collection through literature study and observation. The argument is that shepherds play an essential role in developing the understanding dimension of Generation Z. The first step is to restore self-image with the Family Healing Movement with parents. The second thing is that pastors provide spiritual assistance to develop motivation and improve pastoral services on social media through counseling and training guidance. Her contribution; 1) pastors work together with parents to become inspirations and mediators in recovery, 2) spiritual practitioners take a fundamental part in social media, 3) maximize the pioneering of shepherding young people by new shepherds.